Boost : the science of recharging yourself in an age of unrelenting demands - Gruman, Jamie A.; Healey, Deirdre (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
This is a book about recovery. Not recovery from drugs, alcohol, or surgery, but recovery from the numerous and relentless demands we face in handling our everyday obligations. These demands take a toll on us. Regardless of whether they come from paid employment, caring for young children, looking after elderly parents, or trying to get through graduate school, our daily obligations weigh heavily on us. They deplete our energy. They drain us of motivation. They leave us feeling weary and exhausted. If you tend to feel worn out and want to know how to replenish yourself, this book is for you.We should be able to recover from our daily obligations during our downtime. But many of us don't. In this book we will explain why downtime is inadequate for helping us recharge our batteries, and present you with an effective alternative. Recent scientific developments from around the globe have shed light on the processes that reverse the draining effects of our obligations and help us successfully recover in our leisure time. Not only that, research also reveals that when effective recovery occurs it not only recharges our batteries, but makes us feel happier, makes us healthier, and makes us better at handling the demands that drained us in the first place. We call this boosting to reflect the multi-pronged benefits of successful recovery. In this book we draw on the most cutting-edge science to explain how to transform our ineffective downtime into valuable uptime. Uptime is the time away from our obligations that successfully satisfies the factors that lead us to feel replenished, recharged, recovered, and gives us a boost.
Keywords: Stress management.; Rest.; Self-help -- Self-Management -- Stress Management.; Coping with, advice about mental health issues.; Coping with, advice about stress.; elektronické knihy; electronic books